PEMODELAN DAN PREDIKSI KEBUTUHAN LOGISTIK PASCA BENCANA DI SUMATERA BARAT - Taufik Martha; Purnawan Purnawan; Hendra Gunawan (Rang Teknik Journal, 2021)
Sumatera is one if the areas that is located in the high land. Geographically, it is lied in the volcanic high land that is formed by Bukit barisan Mountain range Sumatera Barat which is rich in natural resources. But unfortunately, due ti its location, West Sumatera has also potentials to various natural disasters like earth quake, tsunami, landslide, land movement, flood and fire if compared to other areas as mentioned in National Action Plan for Disaster Risk Reduction 2012. There have been many preventive actions that have been done by the government. However, those actions are not accompanied by disaster logistics improvement. Modelling is undergone by optimizing the needs pf disaster logistics by considering the characteristics of disaster prone areas. This research is intended to predict the logistics needs by optimizing the needs of disaster victims in west sumatera. The method used is regression analysis by predicting yearly disaster logistics needs. The result of this research showed that the best mode is Y=401.81 + 0.001X1 + 14.55X6 + 37.58X9 – 10.53X14 with the prediction increase of the logistics needs for about 2.3% every year.